The use of speech in the development of geographical reasoning in geography classes (Revista Contexto & Educação, 2023)
The article aims to discuss the use of discourse as an element of mediation in the process of developing geographic reasoning. As a dimension that partially constitutes social relations and material practices, it becomes a fertile field of investigation in geography classes at school. This investigation can help both in the development of geographic thinking and in the objects and phenomena of interest in school geography. Therefore, we sought to discuss its possibilities based on the philosophy of language of the Circle of Mikhail Bakhtin and the Critical Discourse Analysis. At the end, it presents an analysis in character of illustration and deepening from a song in order to elucidate the perspectives adopted around a social problem.